2007
DOI: 10.1001/archotol.133.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Ménière’s Disease in the Finnish Population

Abstract: Patients: The study population comprised 118 patients with symptoms resembling Ménière's disease. The patients were divided into groups based on the diagnostic criteria by the Committee on Hearing and Equilibrium of the American Academy of Otolaryngology-Head and Neck Surgery. Main Outcome Measures: Relatives with Ménière's disease, geographic distribution of birthplaces of grandparents , symptoms, vestibular findings, and audiologic and otoneurologic tests. Results: Approximately 15% of the patients with defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 23 publications
(33 reference statements)
4
34
1
2
Order By: Relevance
“…A recent paper from Finland gives a comparable figure of approx. 15 per cent 24 . In our second paper, also in 1987 25 , we reported 35 first degree relatives from a series of 671 confirmed MD patients (5.4 per cent) rising to an overall frequency of familial cases of 7.7 per cent if second and third degree relatives were included: these figures however were extracted from the family history in clinical records without actual diagnostic confirmation in many of the relatives.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper from Finland gives a comparable figure of approx. 15 per cent 24 . In our second paper, also in 1987 25 , we reported 35 first degree relatives from a series of 671 confirmed MD patients (5.4 per cent) rising to an overall frequency of familial cases of 7.7 per cent if second and third degree relatives were included: these figures however were extracted from the family history in clinical records without actual diagnostic confirmation in many of the relatives.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous reports on familial MD (FMD), [3][4][5][6] the estimated proportion of which in Finland is approximately 15%. 7 In addition to familial clustering, differences in race and population incidences 8 and geographical distribution 2 support the role of genetic factors in the development of MD. A link has been demonstrated between migraine and MD, 9,10 and it has even been suggested that MD develops as a complication of migraine-associated symptoms.…”
mentioning
confidence: 98%
“…48 Klockars e Kentala encontram uma prevalência de 15% de casos de doença de Ménière familiar (DMF) na Finlândia, sendo a grande maioria do sexo feminino. 49 Morrison reporta pela primeira vez antecipação na DMF, ou seja, um aparecimento mais precoce na DMF tendo em conta a idade, assim como uma tendência no aumento da severidade e intensidade dos ataques nas gerações sucessivas de DMF. 50 Estes achados foram suportados mais tarde por estudos efetuados por Fung et al, Oliveira et al e Klockars e Kentala.…”
Section: Fatores Genéticos E História Familiarunclassified
“…50 Estes achados foram suportados mais tarde por estudos efetuados por Fung et al, Oliveira et al e Klockars e Kentala. 49,51,52 Contudo, em algumas famílias esta antecipação não foi observada. 51 Morrison et al documentam uma antecipação, da quinta para a quarta década de vida, no aparecimento da DMF quando comparada com a DM esporádica.…”
Section: Fatores Genéticos E História Familiarunclassified